2012
DOI: 10.1186/1471-2458-12-1117
|View full text |Cite
|
Sign up to set email alerts
|

Perceived coping & concern predict terrorism preparedness in Australia

Abstract: BackgroundIn the aftermath of major terrorist incidents research shows population shifts towards protective behaviours, including specific preparedness and avoidance responses. Less is known about individual preparedness in populations with high assumed threat but limited direct exposure, such as Australia. In this study we aimed to determine whether individuals with high perceived coping and higher concern would show greater preparedness to respond to terrorism threats.MethodsAdults in New South Wales (NSW) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The findings for health/safety and recreational make sense given that key aspects of terrorism-related behavior change relate to lifestyle choices ( Torabi and Seo, 2004 ). The finding for ethical is less clear-cut, but it is possible that this outcome pertains to a greater awareness of order, rules, and increased vigilance, which Stevens et al (2012) found was a commonly reported behavioral response to a perceived terrorist threat.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The findings for health/safety and recreational make sense given that key aspects of terrorism-related behavior change relate to lifestyle choices ( Torabi and Seo, 2004 ). The finding for ethical is less clear-cut, but it is possible that this outcome pertains to a greater awareness of order, rules, and increased vigilance, which Stevens et al (2012) found was a commonly reported behavioral response to a perceived terrorist threat.…”
Section: Discussionmentioning
confidence: 97%
“…Contrastingly, risk as feelings draws upon intuitive reactions that are the outcome of fast associative processing based on experience. This process is guided by heuristics and biased by affective signals ( Slovic et al, 2004 ), self-efficacy ( Stevens et al, 2012 ) and shared normative perceptions ( Goodwin et al, 2005 ). A predominant characteristic of risk as feelings is the influence of affective signals and the motivated behavior that results in order to prolong or avoid experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Protection motivation theory (Maddux & Rogers, ) posits that an individual's preparation is dependent on perceived threat (i.e., likelihood of occurrence) and perceived coping ability (i.e., the ability to do something against the threat), which is the result of self‐efficacy and outcome efficacy, an assumption that is well supported by empirical data (Floyd, Prentice‐Dunn, & Rogers, ). Importantly, it has been shown that preparedness for disaster is affected by efficacy beliefs in various contexts, such as terrorism (Stevens et al., ; Wirtz & Rohrbeck, ) and natural disasters (Wadsworth, Santiago, & Einhorn, ; Whealin, Ruzek, & Southwick, ). The relationship of adjustment processes and self‐efficacy and outcome efficacy has not been addressed in the interviews, but future research needs to address the effect of perceived efficacy of security measures on adjustment processes, since theories of adjustment focusing on primary control (i.e., assimilation) posit that efficacy beliefs, perceived control over outcomes, are central for assimilation (Bak & Brandtstädter, ; Brandtstädter & Renner, ; Riediger & Ebner, ).…”
Section: Discussionmentioning
confidence: 99%
“…Surveys were completed in 45–55 minutes and were conducted by professional interviewers from the NSW Health Survey Program, who also did the transcriptions. Telephone surveys were used to be consistent with other samples in a wider study of disaster‐resilience factors 6 . The validity of telephone‐based interviews to assess stress and anxiety conditions has been demonstrated 7 …”
Section: Methodsmentioning
confidence: 99%
“…Telephone surveys were used to be consistent with other samples in a wider study of disaster-resilience factors. 6 The validity of telephone-based interviews to assess stress and anxiety conditions has been demonstrated. 7…”
Section: Subjects and Administrationmentioning
confidence: 99%